Chapter The Imperial Image of Theoderic: the Case of the Regisole of Pavia - FERRARI, CARLO (Reti Medievali E-Book, 2022)
The contribution intends to retrace the history of Pavia's famous equestrian statue, known as the "Regisole", destroyed in 1796. The statue, in gilded bronze, represented a Roman emperor and was transferred from Rome to Ravenna, most likely by Theoderic. At a certain point, probably between the eighth and tenth centuries, the Regisole arrived in Pavia, even if it is difficult to establish who was responsible for that. The most logical solution is to attribute the transfer of the monument to a Lombard king, specifically to Aistulf, who conquered Ravenna in 751. It is possible to argue that by transferring the Regisole - which was believed to represent Theoderic - to the capital of the Lombard kingdom, Aistulf intended to promote an imperial image of himself, at a time when the conquest of the Exarchate raised him to the rank of "new Theoderic".